(3JhGQjN cGaI GdLKGdbI (B((3HWGQcI GdcdOGf hGdfUGWQI(B)s - (3jhSa dhjS GdSeYGfj,J (B1196 (3g` s
(3ChdgG (B:s
(3GdaUd GdChd , Yf NUhUjGJ GdfUGWQI s
(3BNQgG (B:s
(3hcGf jMed eYg UdjHkG ef fMGS hjUdi CeGeg BNQ GdSeYGfi eLdO (B2 (3, hLg (B493(3BNQ GdcJGH ai JQLeI WjeGJGhS GdHGWQjc s
(3cJHJ ai GdbQf GdJGSY YTQ GdejdGOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdecJHI GdfUQGfjI (B- (3U (B118 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B132 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI HGdehUd (B(17/91) s
Keywords: (3GdJGQjNs